HOTS Through cooperative and inquiry-based learning in PE under the Merdeka curriculum - Dinda Erviani; Mela Suhariyanti; Yopi Hutomo Bhakti; Nurhikmah Bhakti; Dian Daru Cahyo Gumilang (Universitas Suryakancana, 2026)
Physical Education (PE) in the Indonesian Merdeka Curriculum demands learning approaches that extend beyond motor skill acquisition to encompass Higher Order Thinking Skills (HOTS)—specifically the cognitive abilities of analyzing, evaluating, and creating as conceptualized in the revised Bloom's Taxonomy. This study aimed to empirically examine the effectiveness of integrating HOTS through two sequential learning models—Cooperative Learning (Jigsaw type) in Cycle I and Inquiry-Based Learning (IBL) in Cycle II—within a PE setting at the senior secondary school level. A Classroom Action Research (CAR) design based on the Kemmis and McTaggart model was employed across two cycles, each comprising planning, acting, observing, and reflecting phases. Participants were 68 Grade X students (34 per class) from [School Name], [City], selected via purposive sampling based on curricular and academic homogeneity. Data were collected through a validated written HOTS test (20 items; Cronbach's α = 0.82), a structured student activity observation sheet, and an 18-item student perception questionnaire (Likert 5-point scale). Quantitative data were analyzed using descriptive statistics and normalized N-Gain scores; qualitative data from observations and open-ended items were analyzed thematically. Results demonstrated a progressive and significant increase in mean HOTS scores from a baseline of 43.2 to 58.3 at the end of Cycle I and 74.7 at the end of Cycle II (N-Gain Cycle I→II = 0.39, Moderate category). The proportion of students meeting the minimum competency criterion (MCC = 70) rose from 17.6% (baseline) to 76.5% (Cycle II). Active student engagement increased from 61% (Cycle I) to 83% (Cycle II), and 87% of students reported positive perceptions of the integrated learning approach by the end of Cycle II. The study concludes that the sequential integration of Cooperative Learning and IBL constitutes an effective and mutually reinforcing pedagogical strategy for developing HOTS in PE, and is strongly aligned with the Pancasila Student Profile competency dimensions mandated by the Merdeka Curriculum.